Improving Mathematics Learning Achievement of High School Students Through Discovery Learning Model (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
Student learning outcomes at SMAN 2 Konawe Selatan are still low. This is caused by the need for more active participation and involvement of students during the learning process. Teachers need to apply learning methods that can encourage student involvement in learning. The discovery learning model is one method that can meet these expectations. This study aimed to discover that the discovery learning model can improve students' mathematics learning achievement at the senior high school level. This research is a class action research (CAR) with research subjects being students of class XI MIPA 3 semester 1 of SMAN 2 Konawe Selatan in 2021/2022. The data collection method used in this study is the test and observation method. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this study was students of class XI MIPA 3. The data was in the form of formative test results and observation sheets of teaching and learning activities. The results of the analysis found that student achievement increased from cycle I to cycle III, namely, cycle I (50%), cycle II (77%), and cycle III (90%). So it can be concluded that using the discovery learning model can improve students' mathematics learning achievement at the senior high school (SMA) level.